1977
DOI: 10.1007/bf01410888
|View full text |Cite
|
Sign up to set email alerts
|

The use of attainment scaling in the evaluation of a regional mental health program

Abstract: The general evaluation of the success of a regional mental health program was attempted through the use of the Goal Attainment Scale. There were 278 goal guides scored for 96 sample patients at periods of 6, 12, and 18 months after admission. The interrater reliability between pairs of raters at follow-up interviews was high (.87). The intraclass correlation for goal guides constructed by three independent goal setters was moderate (r=.71). The mean scores of the three raters, when compared to a consensus goal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Studies that used a 5-point scale (similar to the approach used herein) reported interrater reliability indices between r = .87 (Kaplan & Smith, 1977) and r = .93 (Schippits & Baxter, 1978 as cited in . Analyses of testretest reliability yielded product moment correlations of r = .84 over a 2-to 3-week period (Woodward, Santa-Barbara, Levin, & Epstein, 1978).…”
Section: Outcome Measuresmentioning
confidence: 97%
“…Studies that used a 5-point scale (similar to the approach used herein) reported interrater reliability indices between r = .87 (Kaplan & Smith, 1977) and r = .93 (Schippits & Baxter, 1978 as cited in . Analyses of testretest reliability yielded product moment correlations of r = .84 over a 2-to 3-week period (Woodward, Santa-Barbara, Levin, & Epstein, 1978).…”
Section: Outcome Measuresmentioning
confidence: 97%
“…Excellent reviews of the reliability and validity of GAS procedures are avail able in Cardillo and Smith (1994) and Smith and Cardillo (1994), respectively. Studies that used a 5-point scale (similar to the approach used herein) reported interrater reliability indices between r = .87 (Kaplan & Smith, 1977) and r = .93 (Schippits & Baxter, 1978;cited in Cardillo & Smith, 1994). Analyses of test-retest reliability yielded product moment correlations of r = .84 over a two to three week period (Woodward, Santa-Barbara, Levin, & Epstein, 1978).…”
Section: Methodsmentioning
confidence: 96%
“…In a critical review, Cytrynbaum, Ginath, Birdwell, and Brandt (1979) reported good interjudge reliability on the GAS; coefficients ranged from .51 to .95. Additional reports of interjudge and interrater reliability found coefficients ranging from .71 to .92 (Beidel, Turner, Bellack, Hersen, & Luber, 1983;Kaplan & Smith, 1977;Kiresuk, 1973;Woodward, Epstein, Santa-Barbara, & Levin, 1980) across samples drawn from schizophrenic patients, community-mental-health-service patients, and family therapy patients. One study of content reliability (i.e., interjudge agreement on scale content) reported ambiguous results, with correlations ranging from Ϫ.27 to .64.…”
Section: Psychometric Properties Of the Gasmentioning
confidence: 94%